2003
DOI: 10.1111/j.1944-9720.2003.tb02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Using an E‐Mail Exchange to Promote Cultural Learning

Abstract: This study describes an intercultural e‐mail exchange at the college level. Students in a beginning Spanish class in the United States and an intermediate English as a second language class in Mexico corresponded weekly for one semester. The U.S. students also wrote reflective papers and completed surveys before and after the exchange regarding their attitudes toward their own and Mexican cultures and their perceptions of the exchange itself. Quantitative and qualitative data from these papers and surveys are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…The use of multimedia (e.g., the Internet, e-mail, DVDs, radio broadcasts, and L2 satellite television programs) can provide an interactive framework for incorporating Cultures Standards 2.1 and 2.2 into the language classroom. Both Lee (1997) and Hertel (2003) discussed the role of the Internet in integrating culture into the foreign language classroom. Hertel (2003), for example, described the use of an email exchange program to promote cultural learning between a university-level beginning Spanish class in the United States and an intermediate English as a second language (ESL) class in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multimedia (e.g., the Internet, e-mail, DVDs, radio broadcasts, and L2 satellite television programs) can provide an interactive framework for incorporating Cultures Standards 2.1 and 2.2 into the language classroom. Both Lee (1997) and Hertel (2003) discussed the role of the Internet in integrating culture into the foreign language classroom. Hertel (2003), for example, described the use of an email exchange program to promote cultural learning between a university-level beginning Spanish class in the United States and an intermediate English as a second language (ESL) class in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers investigated the role of computer network in the language classes that it was operated by microcomputer and also use for the concept of communicative competence, the notional/functional syllabi, and language teaching methodologies based on the Communicative Approach (Tell & Kelm, as cited in Liaw, 1998, p. 336). Survey showed that network computers can improve students writing skills (Hertel, 2003). Kroonenberg (1995) claim that second language learners, who were shy and lacked confidence in speaking in class can express themselves by using computer media.…”
Section: The Role Of the Computers On Language Learners Communicationmentioning
confidence: 99%
“…Studies have shown that asynchronous CMC with native speakers in foreign language classrooms is a valuable tool for language learning (Abrams, 2003;Beauvois, 1997;Call & Sotillo, 1995;Hertel, 2003;Oliva & Pollastrini, 1995;Schwartz, 1993) placing the language learners in contact with real audiences, and providing them with authentic language experiences (Urdal, et al, 1996). Studies have also shown that asynchronous CMC is a useful means for promoting cross-cultural communication, although it may sometimes hinder learners' perceptions of the target culture (Meagher & Castan˜ os, 1996) and may even impede intercultural communication (Ting-Toomey, 1999).…”
Section: Introductionmentioning
confidence: 99%